2013
DOI: 10.1155/2013/430239
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Implicated in the Immunopathogenesis of Lupus Nephritis

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the deposition of immune complexes due to widespread loss of immune tolerance to nuclear self-antigens. Deposition in the renal glomeruli results in the development of lupus nephritis (LN), the leading cause of morbidity and mortality in SLE. In addition to the well-recognized genetic susceptibility to SLE, disease pathogenesis is influenced by epigenetic regulators such as microRNAs (miRNAs). miRNAs are small, noncoding RNAs that bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 112 publications
(137 reference statements)
1
20
0
Order By: Relevance
“…These mechanisms may affect DNaseI production through gene silencing independently or even in combination. In line with such hypothesis, different miRNA profiles were found in kidney of lupusprone mice with glomerulonephritis as well as in biopsies of lupus patients [35,67,68].…”
Section: Can Epigenetic Mechanisms Explain the Onset Of Tissue Damage?supporting
confidence: 58%
“…These mechanisms may affect DNaseI production through gene silencing independently or even in combination. In line with such hypothesis, different miRNA profiles were found in kidney of lupusprone mice with glomerulonephritis as well as in biopsies of lupus patients [35,67,68].…”
Section: Can Epigenetic Mechanisms Explain the Onset Of Tissue Damage?supporting
confidence: 58%
“…miRNAs play a key role in the activation of innate immunity and the regulation of adaptive immune responses29. In this study, we intended to examine whether immunosuppressant or ASC treatment can modify disease-associated miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has demonstrated that miRNAs play a vital role in autoimmunity [14,15], and in LN in particular [16]. Recently, Liu et al demonstrated that miR-30a was significantly increased in B cells from SLE patients, and overexpressed miR-30a in vitro could lower the level of Lyn, a member of the Src family protein tyrosine kinases, in B cells [17].…”
Section: Pathogenesis Of Lupus Nephritismentioning
confidence: 99%